Penerapan Teknologi Video Pembelajaran Jarak Jauh Mengenai Kewirausahaan dan Pemanfaatannya Sebagai Media Edukasi bagi Remaja SMAN 3 Batusangkar, Sumatera Barat - Danny Hidayat; Ullya Rahmi Aswin; Donard Games; Dessy Kurnia Sari; Laura Amelia Triani; Silmi Silmi; Hanalde Andre; Prima Fithri (Warta Pengabdian Andalas, 2023)
This paper discusses the assistance of implementing long-distance video learning technology in entrepreneurship and its utilization as an educational tool for teenagers at SMAN 3 Batusangkar, West Sumatra. Entrepreneurship education is becoming increasingly crucial in globalization and information technology development. However, access to relevant and high-quality learning materials is often limited in remote areas. This activity aims to evaluate the effectiveness of using long-distance video learning technology as a supportive tool in entrepreneurship education in a high school setting. The activity started with data collection through interviews and observations of students and teachers involved in the learning process. The results indicated that long-distance video learning technology positively impacts students' understanding of entrepreneurship concepts. Students responded positively to the more interactive and engaging learning approach provided by video learning. In addition, teachers reported increased student motivation and participation in entrepreneurship education. In the context of SMAN 3 Batusangkar, long-distance video learning technology provides an opportunity to overcome resource limitations and access high-quality learning materials. The study also notes some challenges, such as varying internet connection quality and the need for further teacher training to integrate this technology into the curriculum. This community service highlights the importance of using technology as an innovative and effective learning tool to teach entrepreneurship concepts to the younger generation.